2015
DOI: 10.1002/ppap.201400181
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Few‐Layer Graphene‐on‐Insulator Films by Controllable C4F8 Plasma Etching SiC

Abstract: C 4 F 8 -based, inductively coupled plasma (ICP) combined with dual-frequency capacitively coupled plasma (CCP) was used to etch 6H-SiC substrates for the synthesis of few-layer graphene-on-insulator (FLGOI) films. The Raman spectroscopy studies were used to measure the thickness of the FLG samples. The combination of high frequency CCP and ICP modes can facilitate the tuning of the C 4 F 8 discharge dissociation characteristics. A balance is struck between etching and deposition, leaving an ultra-thin C-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…on/in the silicon carbide substrate. As of today, there is a fairly large variety of techniques for the processing of silicon carbide that allow, to some extent, to solve the following problem: wet etching; etching in solvents, stimulated by femtosecond laser; plasma etching; etching in plasma atmospheric discharge; plasma jet processing, and etc [15][16][17][18][19][20][21][22][23][24][25] . The choice of silicon carbide processing method is determined by the specific target, but nevertheless any of the methods must meet a number of general requirements: minimal defect formation on the surface of the etched profile, high etching rates, and high directionality of the processed window during the etching process.…”
mentioning
confidence: 99%
“…on/in the silicon carbide substrate. As of today, there is a fairly large variety of techniques for the processing of silicon carbide that allow, to some extent, to solve the following problem: wet etching; etching in solvents, stimulated by femtosecond laser; plasma etching; etching in plasma atmospheric discharge; plasma jet processing, and etc [15][16][17][18][19][20][21][22][23][24][25] . The choice of silicon carbide processing method is determined by the specific target, but nevertheless any of the methods must meet a number of general requirements: minimal defect formation on the surface of the etched profile, high etching rates, and high directionality of the processed window during the etching process.…”
mentioning
confidence: 99%
“…Plasma treatment of graphene surfaces has been shown to successfully modify the basal plane of graphene without the creation of harsh by-products [8] [9] [10] [11]. Plasma modi cation of graphene utilizes energetic and/or reactive radicals in the plasma to interact with the surface and can have several effects, such as breaking the C-C bonds, removing surface atoms, "cleaning" the surface, and modifying the surface chemistry [12]. The surface reactions are determined by the types of plasma species and energy, which depend on the plasma system, source gas and pressure, and excitation power.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have used plasma treatments of SiC for graphene growth. [20][21][22][23][24][25] For example, Raghavan et al reported that the surface chemistry using CF 4 -and Cl 2 -based inductively coupled plasma-reactive ion etching of a SiC(0001) surface followed by thermal annealing has the potential to yield a large-area graphene film. 20 A C 4 F 8 -based fluorocarbon plasma was also used to etch a Si-face SiC surface prior to annealing in an Ar gas for nucleating and growing graphene films.…”
Section: Introductionmentioning
confidence: 99%
“…20 A C 4 F 8 -based fluorocarbon plasma was also used to etch a Si-face SiC surface prior to annealing in an Ar gas for nucleating and growing graphene films. 21,22 Tsai et al exposed a SiC surface to N 2 plasma to promote the reaction of nitrogen ions with Si, which was followed by annealing at 1150°C in a N 2 /H 2 atmosphere. 23 The objectives of these studies were to form graphene at lower temperatures than those required for simple Si sublimation.…”
Section: Introductionmentioning
confidence: 99%